Analysing Scaffolds in Learning Systems Concepts in School Biology. (January 2023) - Singh, Garima; Khunyakari, Ritesh
Learning about components and processes of complex biological systems is challenging and requires abstraction through mediational tools such as text, visuals, models and visualisation experiences. The 'systems concepts' necessitate building coherent relations and anticipating consequences, requiring greater mediational support. This article reports findings from two components of a study. The first component involved a comparative analysis of textbooks and revealed weak links between visuals and other scaffolding tools such as activities and end-chapter exercises. Visuals in textbooks were found to be inadequate, inappropriate and often potential sources of confusion. The second component of the study involved drawing-based task that elicited learner struggles in internalising ideas about the human digestive system. The study calls for a refined understanding and use of mediational tools towards bridging the gaps between conceptual models and learners' mental models. The study opens avenues for further inquiry that could support learning biology.